Structure and properties of Cr-, Zr-, Ti-electrospark coatings on iron - Lobachova Galyna G.; Ivashchenko Ievgen V. (Металознавство та обробка металів, 2019)
The effect of the intermediate layer of iron in electric-spark doping with transition metals (Zr, Ti, Cr) was investigated, which contributes to the formation of coatings enriched with penetration phases on the surface, which improves surface properties (microhardness up to 7.5 GPa and wear resistance 10.41 times).